(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This scientific article examines the importance of modern technologies in improving the process of English language teaching and learning in contemporary education systems. In recent years, globalization, digitalization, and the rapid development of information technologies have significantly influenced foreign language education. English has become an international language of communication, science, technology, and business; therefore, effective methods of teaching English are increasingly important in educational institutions.